Pharmacokinetics, Pharmacodynamics, and Immunogenicity of Belatacept in Adult Kidney Transplant Recipients - Shen, Jinshan (Springer International Publishing, 2013)
BACKGROUND AND OBJECTIVES: Belatacept is a first-in-class, selective co-stimulation blocker recently approved for the prophylaxis of organ rejection in adult kidney transplant recipients. The objective of this study was to report the pharmacokinetics, pharmacodynamics, and immunogenicity of belatacept. METHODS: The pharmacokinetics, pharmacodynamics (CD86 receptor occupancy), and immunogenicity of belatacept were studied in de novo adult kidney transplant recipients in phase II and III clinical studies. RESULTS: Following multiple doses of 5 or 10 mg/kg, the geometric mean (percentage coefficient of variation) maximum serum concentration and area under the serum concentration–time curve over one dosing interval of belatacept were 136 (20 %) and 238 (27 %) μg/mL, and 13,587 (27 %) and 21,241 (35 %) μg·h/mL, respectively. The median belatacept elimination half-life was 8–9 days. Belatacept exhibited concentration-dependent binding to CD86 receptors. The pre-dose CD86 receptor occupancy by belatacept decreased from 94 to 65 % between day 5 and 1 year post-transplant, with corresponding pre-dose trough serum concentrations of belatacept decreasing from ~35 to 4 μg/mL during this period. The cumulative incidence of developing anti-belatacept antibodies was 5.3 % up to 3 years post-transplant and had no impact on belatacept exposure. CONCLUSIONS: Belatacept in adult kidney transplant demonstrated linear pharmacokinetics with low variability, concentration-dependent pharmacodynamics, and a low incidence of anti-drug antibodies.